2022
DOI: 10.4054/demres.2022.46.3
|View full text |Cite
|
Sign up to set email alerts
|

Parental education, divorce, and children’s educational attainment: Evidence from a comparative analysis

Abstract: BACKGROUNDChildren who experience parental divorce have worse long-term educational attainment than children living in intact families. Less clear is the extent to which heterogeneity in the divorce penalty depends on parents' socioeconomic background and contextual characteristics. OBJECTIVEThis study focuses on the negative consequences of parental divorce for children's tertiary education attainment, their heterogeneity by parental socioeconomic background, and variation across time and space. METHODSingle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is important to note that mental health and well-being declines in children affected by parental divorce may be due to other changes, such as changes in housing and social and economic changes that accompany breakups (Leopold & Kalmijn, 2016). In terms of education, children of divorced parents are less likely to attain higher levels of education and also exhibit lower academic achievement in reading and mathematics compared to peers with intact families long-term (Guetto et al, 2022;Anthony et al, 2014). Preschool students with divorced parents also showed more negative classroom behaviours than their peers (Amca Toklu, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that mental health and well-being declines in children affected by parental divorce may be due to other changes, such as changes in housing and social and economic changes that accompany breakups (Leopold & Kalmijn, 2016). In terms of education, children of divorced parents are less likely to attain higher levels of education and also exhibit lower academic achievement in reading and mathematics compared to peers with intact families long-term (Guetto et al, 2022;Anthony et al, 2014). Preschool students with divorced parents also showed more negative classroom behaviours than their peers (Amca Toklu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of preschool students, researchers found that children with divorced parents displayed higher aggression and less positive behaviours in the classroom, suggesting that the effects of divorce are present in young children in early education (Amca Toklu, 2022). Beyond early education, the effects of divorce span into the college and university years of young adulthood (Guetto et al, 2022). Interestingly, children of divorced parents overall have lower educational attainment and are less likely to attend college or university.…”
Section: Educational Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For both Europe and the US, there is ample empirical evidence to suggest that children of divorce and separation, or those living with a single parent at birth, fare worse in terms of educational outcomes than children living with both parents (Amato, 2000 , 2010 ; Guetto et al, 2022 )—what we refer to as the ‘non-intact penalty’. Recent research in this field has followed two main lines of inquiry.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A bulk of empirical research has shown that growing up in a single-parent household is associated with adverse child outcomes in several domains, such as psychological well-being and health (Härkönen et al, 2017 ). These negative consequences also involve short-term educational performances (Amato & Anthony, 2014 ; Radl et al, 2017 ) and long-term educational attainment, such as the probability of obtaining a tertiary degree (Bernardi & Radl, 2014 ; Guetto et al, 2022 ), which can lead to an accumulation of disadvantages over the life course.…”
Section: Introductionmentioning
confidence: 99%